Plasma total homocysteine is not associated with peripheral neuropathy in a groups Bangladeshi type 2 diabetic subjects - Rahman, MM; Hassan, Z; Biswas, KB; Bhowmik, NB; Ali, L (Bangladesh Journal of Medical Science, 2012)
Aims: The present study was undertaken to explore the relationship of plasma homocysteine in the pathogenesis of neuropathy in diabetic patients. Subjects and Methods: Forty two type 2 diabetic patients [22 with neuropathy (DN group) and 20 without neuropathy (DNN group)], age range between 35-70 years had relatively controlled glycemia and duration of diabetes 7-15 years, were studied. Motor and sensory nerve conduction velocities and action potential amplitudes of peripheral nerves were determined by following standard protocol. HbA1c was estimated by modified HPLC (BIO-RAD Variant, USA). Serum C-peptide was measured by enzyme linked immunosorbentassay (ELISA), plasma total homocysteine by Fluorescent Polarization Immunoassay (FPIA). Results: Age, BMI and blood pressure of the study subjects were. Duration of diabetes between DN and DNN groups was comparable. DN group had significantly higher fasting glucose levels (9.8±3.8, mmol/l) compared to the DNN group (6.9±1.8, p=0.004). This trend was also reflected in the HbA1c level: 8.7± 2.1 vs 7.2±1.6 in DN group and DNN group respectively (p=0.009). The two diabetic groups had relatively higher absolute C-peptide level compared to the controls (p=ns). DN and DNN groups had significantly higher plasma homocysteine level compared to the Controls. But between the two diabetic groups no significant difference was observed. Ulnar and peroneal motor nerve conduction velocities and compound muscle action potentials in the diabetic neuropathy group significantly lower compared to diabetic counterpart and the controls. Ulnar and sural sensory nerve conduction velocities and action potentials were significantly lower in the diabetic neuropathy group compared to the diabetic counterpart and the controls. Plasma homocysteine did not show any correlation with nerve conduction velocities and action potential amplitudes. Conclusions: The data concluded that (i) Diabetic neuropathy may not be related to hyperhomocysteinemia in type 2 diabetic patients of Bangladeshi origin; (ii) Hyperglycemia, even at milder level, is related to neuronal dysfunction in these subjects; and (ii) Hyperinsulinemia don't seem to be prerequisite for neuropathy in these subjects. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12607 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12